Bedside terminals and quality of nursing documentation... part 1. - Marr PB; Duthie E; Glassman KS; Janovas DM; Kelly JB; Graham E; Kovner CT; Rienzei A; Roberts NK; Schick D (Computers in Nursing)
In this article, the authors report on part one of a three-part investigation studying the impact of bedside terminals at New York University Medical Center, New York, NY. Using a before-after parallel control-group design, the quality of computerized nursing documentation was studied before and after adding computers to patient rooms. The quality of documentation was defined by timeliness and completeness of data. The study hypothesis, which predicted a positive relationship between the presence of bedside terminals and the quality of nursing documentation, was not supported. Study results showed a minimal use of the computer terminals located in patient rooms. A surprising result was the use of terminals located in rooms other than that of the patient for which documentation was made.